2010
DOI: 10.1371/journal.pone.0010202
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of MTT and MTS-Based Assays for Measurement of Antiproliferative Activity of Green Tea Polyphenols

Abstract: BackgroundThe chemopreventive effect of green tea polyphenols, such as (-)-epigallocatechin-3-gallate (EGCG), has been well demonstrated in cell culture studies. However, a wide range of IC50 concentrations has been observed in published studies of the anti-proliferative activity of EGCG from different laboratories. Although the susceptibility to EGCG treatment is largely dependent on cancer cell type, the particular cell viability and proliferation assays utilized may significantly influence quantitative resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
263
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(283 citation statements)
references
References 21 publications
16
263
0
4
Order By: Relevance
“…The MTS assay data indicate that unlabelled IPP and LKP was not cytotoxic in Caco-2 or HepG2 cells from 0.1-10mM at selected time points. The MTS assay yielded low errors, similar to the findings of others (30). A positive control, Triton®-X-100 (0.05%), massively reduced viability of both cell types at each incubation time point.…”
Section: Ipp and Lkp Are Not Cytotoxic In Vitro: Mts And Histologysupporting
confidence: 84%
“…The MTS assay data indicate that unlabelled IPP and LKP was not cytotoxic in Caco-2 or HepG2 cells from 0.1-10mM at selected time points. The MTS assay yielded low errors, similar to the findings of others (30). A positive control, Triton®-X-100 (0.05%), massively reduced viability of both cell types at each incubation time point.…”
Section: Ipp and Lkp Are Not Cytotoxic In Vitro: Mts And Histologysupporting
confidence: 84%
“…The reason for these different results is not yet understood, especially because similar tests (MTT and MTS) lead to very different results. 129 However, such models offer an inexpensive and high-throughput alternative to in vivo research strategies. It is of utmost importance to enhance quality and reliability of in vitro studies with nanoparticles in general.…”
Section: Spions In In Vitro Assaysmentioning
confidence: 99%
“…The MTT assay can overestimate the number of viable cells in comparison to ATP measurements and exhibits an IC 50 that is two-fold higher 43 . Furthermore, Petty and colleagues reported that the ATP assay could detect the lower limit of 1563 cells per well whereas the MTT assay could not detect fewer than 25k cells/well 12 .…”
Section: Discussionmentioning
confidence: 99%